Treatment switches during pregnancy among HIV-positive women on antiretroviral therapy at conception - Huntington, Susie E (2011)
OBJECTIVES: To describe antiretroviral therapy (ART) use and clinical status, at start of and during pregnancy, for HIV-positive women receiving ART at conception, including the proportion conceiving on drugs (efavirenz and didanosine) not recommended for use in early pregnancy. METHODS: Women with a pregnancy resulting in a live birth after 1995 (n=1,537) were identified in an observational cohort of patients receiving HIV care at 12 clinics in the UK by matching records with national pregnancy study data. Treatment and clinical data were analysed for 375 women conceiving on ART, including logistic regression to identify factors associated with changing regimen during pregnancy. RESULTS: Of the 375 women on ART at conception, 39 (10%) conceived on dual therapy, 306 (82%) on triple therapy and 30 (8%) on >3 drugs. In total, 116 (31%) women conceived on a regimen containing efavirenz or didanosine (69 efavirenz, 54 didanosine, 7 both). Overall, 38% (143) switched regimen during pregnancy, of whom 41% (n=48) had a detectable viral load (≥50 copies/ml) around that time. Detectable viral load was associated with increased risk of regimen change (adjusted odds ratio 2.2, 95% confidence interval [1.3, 3.8]), while women on efavirenz at conception were three times more likely to switch than women on other drugs (3.3, [1.8, 6.0]). Regimen switching was also associated with calendar year at conception (0.9, [0.8-1.0]). CONCLUSIONS: These findings reinforce the need for careful consideration of ART use among women planning or likely to have a pregnancy in order to reduce viral load before pregnancy and avoid drugs not recommended for early antenatal use.